Application of Light Reflection Method to Observe DNAPL Movement in Different Soil Media - Alazaiza, M. Y. D.; Ngien, S. K.; Mustafa, M. Bob; Samira, A. Kamaruddin; Wan Faizal, Wan Ishak (Universiti Malaysia Pahang, 2016)
In this research, the behaviour of dense non-aqueous phase liquid (DNAPL) was observed in different unsaturated porous media using light reflection method (LRM). Natural sand was used as a porous media that was collected from a river and segregated into different sizes through sieving. Three different sizes of the sand were used in this study. The sands were packed separately in rectangular acrylic columns and then DNAPL was injected from the top of the column. Tetrachloroethylene (PCE) was used as the DNAPL, and it was observed using a digital camera connected to a laptop and controlled using special software. The findings show a significant difference in the migration of PCE through these sands. The migration of PCE in Experiment 3 was much faster than the migration in the other experiments. This is most likely due to the large pores in the sand samples. LRM provides a non-intrusive and nondestructive tool for studying fluid flow for which rapid changes in fluid flow in the entire flow domain is difficult to measure using conventional techniques.